Cultural Studies after the End of the World?: Introducing Vol. 13 No. 2 - Kim, Min Seong (Retorik: Jurnal Ilmu Humaniora, 2025)
The present issue of Retorik was envisioned as the second installment of the special volume celebrating the twenty-fifth anniversary of the Graduate Program in Cultural Studies at Sanata Dharma University. While Vol. 13, No. 1—featuring a guest editorial by one of the founders of the Program, Dr. Stanislaus Sunardi—comprises six articles from alumni of the Program who were invited to contribute, several articles included in this issue, Vol. 13, No. 2, are responses to an open call for papers circulated in April 2025. The theme of the CfP was: “Cultural Studies after the End of the World,” or, in the Indonesian version, “Kajian Budaya Setelah Kiamat.” Of course, what is meant by “the end of the world”—deliberately rendered with theological undertones in the Indonesian version, i.e., as “kiamat” (apocalypse) rather than the more neutral “akhir dunia”—merits some clarification.